Planning documents as an element of modernizing the urban structure of the Poznań metropolitan area = Dokumenty planistyczne jako element modernizacji struktury urbanistycznej poznańskiego obszaru metropolitalnego - Bonenberg, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a report on studies concerning the role of planning documents in the modernization process of the Poznań metropolitan area (PMA). Over the last 25 years, dynamic social, economic and spatial changes have taken place in this area, which is becoming an increasingly integrated place combining living, work and leisure for a million residents. Emerging challenges regarding the functional, spatial and infrastructural modernization of the PMA call for new planning methods.
Keywords: poznański obszar metropolitalny; modernizacja struktur urbanistycznych; dokumenty planistyczne; Poznań Metropolitan Area; modernization of urban structures; planning documents